Recovery and utilization of low-grade waste heat in the oil-refining industry using heat engines and heat pumps: an international technoeconomic comparison - Gangar,N; Macchietto,S; Markides,C (Energies, 2020)
We assess the technoeconomic feasibility of onsite electricity and steam generation from recovered low-grade thermal energy in oil refineries using organic Rankine cycle (ORC) engines and mechanical vapour compression (MVC) heat pumps in various countries. The efficiencies of 34 ORC and 20 MVC current commercial systems are regressed against modified theoretical models. The resulting theoretical relations predict the thermal efficiency of commercial ORC engines within 4–5% and the coefficient of performance (COP) of commercial MVC heat pumps within 10–15%, on average. Using these models, the economic viability of ORC engines and MVC heat pumps is then assessed for 19 refinery streams as a function of heat source and sink temperatures, and the available stream thermal energy, for gas and electricity prices in selected countries. Results show that: (i) conversion to electrical power with ORC engines is, in general, economically feasible for heat-source temperatures >70 C, however with high sensitivity to energy prices; and (ii) steam generation in MVC heat pumps, even more sensitive to energy prices, is in some cases not economical under any conditions—it is only viable with high gas/low electricity prices, for large heat sources (>2 MW) and higher temperatures (>140 C). In countries and conditions with positive economics, payback periods down to two years are found for both technologies.